The Prevalence of Sarcopenia and Its Impact on Clinical Outcomes in Lumbar Degenerative Spine Disease—A Systematic Review and Meta-Analysis - Wu, Wei-Ting; Lee, Tsung-Min; Han, Der-Sheng; Chang, Ke-Vin (Journal of clinical medicine, 2021)
The association of sarcopenia with poor clinical outcomes has been identified in various medical conditions, although there is a lack of quantitative analysis to validate the influence of sarcopenia on patients with lumbar degenerative spine disease (LDSD) from the available literature. Therefore, this systematic review and meta-analysis aimed to summarize the prevalence of sarcopenia in patients with LDSD and examine its impact on clinical outcomes. The electronic databases (PubMed and Embase) were systematically searched from inception through December 2020 for clinical studies investigating the association of sarcopenia with clinical outcomes in patients with LDSD. A random-effects model meta-analysis was carried out for data synthesis. This meta-analysis included 14 studies, comprising 1953 participants. The overall prevalence of sarcopenia among patients with LDSD was 24.8% (95% confidence interval [CI], 17.3%–34.3%). The relative risk of sarcopenia was not significantly increased in patients with LDSD compared with controls (risk ratio, 1.605; 95% CI, 0.321–8.022). The patients with sarcopenia did not experience an increase in low back and leg pain. However, lower quality of life (SMD, −0.627; 95% CI, −0.844–−0.410) were identified postoperatively. Sarcopenia did not lead to an elevated rate of complications after lumbar surgeries. Sarcopenia accounts for approximately one-quarter of the population with LDSD. The clinical manifestations are less influenced by sarcopenia, whereas sarcopenia is associated with poorer quality of life after lumbar surgeries. The current evidence is still insufficient to support sarcopenia as a predictor of postoperative complications.